Supply Chain Management Practices Influence Supply Chain Performance With Mediation Role of Innovation and Moderation Role of Top Management Support - Xu, Heyan; Zhao, Changheng (Frontiers in Public Health, 2022)
The study focuses on supply chain management practices, innovation, top management commitment, and supply chain performance at companies. The study's main objective is to investigate the association between supply chain management practices and supply chain performance and the intervening effect of innovation, the interaction effect of top management commitment. In this study, a simple random sampling technique and the sample size selected with G* power software (N = 208). The readymade questionnaire was used to collect data from National Logistic Corporation (NLC), Food and Beverage Companies Groups (FMCG) at China. The data analyzed through Smart-PLS (SEM → small and medium enterprises) and SPSS software. Meanwhile, innovational significant and positively mediated the relationship between supply chain management five practices and organizational performance. The findings of this study will help managers of SMEs enhance their performance. The results showed that SCMP directly and significantly affected supply chain performance, and customer relationship management was insignificant with supply chain performance. Supplier and customer relationship management both have a significant impact on innovation. In addition, innovation is considered a significant positive predictor for supply chain performance with the intervening approach. But top management commitment proved insignificant for customer relationship management and supply chain performance. The study further concluded that supply chain management practices would not be productive for supply chain performance if the top management does not apply innovative technologies in the organizations.